Energy and exergy analysis of vapour compression refrigeration system using selected eco-friendly hydrocarbon refrigerants enhanced with tio2-nanoparticle - Ajuka, Luke; Odunfa, Moradeyo; Ohunakin, Olayinka; Oyewola, Miracle (International Journal of Engineering and Technology, 2017)
The experimental study investigated the energy and exergy performance of a domestic refrigerator using eco-friendly hydrocarbon refrigerants R600a and LPG (R290/R600a: 50%/50%) at 0, 0.05, 0.15 and 0.3wt % concentrations of 15nm particle size of TiO2 nano-lubricant, and R134a. The effects of evaporator temperature on power consumption, coefficients of performance, exergetic efficiency and efficiency defects in the compressor, condenser, capillary tube and evaporator of the system were examined. The results showed that LPG + TiO2 (0.15wt %) and R600a + TiO2 (0. 15wt %) had the best of performances with an average of 27.6% and 14.3% higher coefficient of Performance, 34.6% and 35.15% lower power consumption, 13.8% and 17.53% higher exergetic efficiency, a total exergetic defect of 45.8% and 64.7% lower compared to R134a. The exergetic defects in the evaporator, compressor, condenser, and capillary tube were 38.27% and 35.5%, 49.19% and 55.56%, 29.7% and 33.7%, 39.1% and 73.8% lower in the system when compared to R134a respectively. Generally, the refrigerants with nano-lubricant mixture gave better results with an appreciable reduction in the exergy defect in the compressor than the pure refrigerants, and LPG + TiO2 (0. 15wt %) gave the best result in the refrigeration system based on energy and exergy analysis.